APLIKASI KEAMANAN PESAN MENGGUNAKAN ALGORITMA STEGANOGRAFI DAN KRIPTOGRAFI - Wawan Setiawan; Juwairiah Juwairiah; Herry Sofyan (Telematika, 2012)
Steganography is a technique of hiding a secret or confidential information in another message so that other people are not aware of the existence of a hidden message. In order for hidden messages or information that it's safer to use the science of cryptography for data encryption. So that the data or messages can not be understood by an unauthorized person who managed to access the data. This application uses methodologies Rappid Guidelines for Application Engineering (Grapple), which consists of Requirement gathering, Analysis, Designs, Development, and Deployment. This application was built using the Java programming language with tools NetBeans IDE 7.0. The algorithm used in this application is the steganography algorithms Least Significant Bit and cryptographic algorithms Vigenere Cipher. The final results of this study is an application of steganography in images by using the method of least significant bit (LSB) and vigenere that can be run on a computer. The image can be used in this application is the image format JPG, PNG, GIF, and BMP. This application can insert text in the image and can perform encryption and decryption at the message you want to insert.